2002
DOI: 10.1002/ptr.786
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic biliary obstruction: can silymarin protect liver function?

Abstract: The hepatoprotective property of silymarin is well known. However, it is not known whether the antioxidant silymarin might have a beneficial effect in extrahepatic cholestasis in common bile duct ligated rats. Malonaldehyde property concentrations, the hydrogen-donating ability and reducing power were measured in liver homogenates by spectrophotometry, as well as free SH-group levels and glutathione-reductase activities in sera. The total scavenger capacity of the livers was quantified by a chemiluminometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…Many studies reported that anti-inflammatory and antioxidant agents may show beneficial effect on persistent inflammation and oxidative damage in cholestasis [1,7,8,11]. But most of these agents are in experimental process and are not ready for clinical usage.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many studies reported that anti-inflammatory and antioxidant agents may show beneficial effect on persistent inflammation and oxidative damage in cholestasis [1,7,8,11]. But most of these agents are in experimental process and are not ready for clinical usage.…”
Section: Introductionmentioning
confidence: 97%
“…This condition causes known biochemical, pathophysiological and morphological abnormalities produced by interrupted enterohepatic circulation, obstructed hepatic biliary tree, increased biliary pressure, retention of biliary constituents and impairment of hepatocellular transport. In some circumstances, such as biliary atresia, despite early diagnosis and prompt surgical intervention to improve biliary drainage, most patients will either require liver transplantation or die as a result of progressive liver fibrosis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proved to have a protective effect against experimental hepatotoxicity by regulating the actions of the ultrastructures of the liver cells and improving the activities of hepato-cellular enzymes and bile production (Hagymasi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin is a standardized mixture of antioxidant flavonolignans (silybin and silibinin) extracted from the medicinal plant Silybum marianum. It is a free radical scavenger and a membrane stabilizer that prevents lipoperoxidation induced cell damage [9] and was proved to have a protective effect against experimental hepatotoxicity [10]. Moreover, alternative beneficial effects of silymarin comprising cardioprotective, antidiabetic, antiinflammatory, and iron chelating were recently demonstrated [11][12][13].…”
mentioning
confidence: 99%